2020
DOI: 10.1016/j.neo.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting methyltransferase PRMT5 retards the carcinogenesis and metastasis of HNSCC via epigenetically inhibiting Twist1 transcription

Abstract: Protein arginine methyltransferase 5 (PRMT5) is an important type II arginine methyltransferase that can play roles in cancers in a highly tissue-specific manner, but its role in the carcinogenesis and metastasis of head and neck squamous cell carcinoma (HNSCC) remains unclear. Here, we detected PRMT5 expression in HNSCC tissues and performed series of in vivo and in vitro assays to investigate the function and mechanism of PRMT5 in HNSCC. We found that PRMT5 was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…PRMT5 promotes the metastasis of laryngeal carcinoma by activating Wnt4/β -catenin signaling pathway (Wang et al, 2020). Inhibition of PRMT5 reduces the transcription of Twist 1 mediated by H3K4me3 and delays the metastasis of squamous cell carcinoma of head and neck (Fan et al, 2020). Moreover, macrophage-capping protein (CAPG) has been shown to promote cancer metastasis, STC-1 enhances the invasion of cancer cells by activating PI3K pathway.…”
Section: Other Signaling Pathwaysmentioning
confidence: 99%
“…PRMT5 promotes the metastasis of laryngeal carcinoma by activating Wnt4/β -catenin signaling pathway (Wang et al, 2020). Inhibition of PRMT5 reduces the transcription of Twist 1 mediated by H3K4me3 and delays the metastasis of squamous cell carcinoma of head and neck (Fan et al, 2020). Moreover, macrophage-capping protein (CAPG) has been shown to promote cancer metastasis, STC-1 enhances the invasion of cancer cells by activating PI3K pathway.…”
Section: Other Signaling Pathwaysmentioning
confidence: 99%
“…The forkhead box (FOX) family, composed of proteins that share related winged helix-turn-helix DNA binding motifs, belongs to the “winged helix” superfamily [ 13 ]. FOX genes are widely present in the evolution of vertebrates and invertebrates, involved in many molecular cascades and regulation of biological functions, such as embryonic development, cell cycle regulation, early morning metabolism control, and signal pathway transduction [ 14 ]. FOXD1 dysfunction has been linked to different pathologies, which constitutes diagnostic biomarker and becomes a promising target for future treatment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,49 Although PRMT5 is a major type II PRMTs that specifically deposits SDMA marks on histone H3 at arginine 8 (H3R8me2s) and histone H4 at arginine 3 (H4R3me2s), and these two marks are associated with transcriptional repression. [50][51][52] We demonstrated that inhibition of PRMT1 by ribavirin caused a significant decrease of PRMT1 enrichment, whereas inhibition of PRMT5 by ribavirin caused a significant increase of PRMT5 enrichment in VEGF gene. These findings suggested that ribavirin repressed transcription of VEGF through PRMT1 and PRMT5, and the VEGF gene regulated by PRMT1 and PRMT5 was further confirmed by measurement of its mRNA levels in ascites tumour treated with ribavirin.…”
Section: Discussionmentioning
confidence: 81%